Enantioconvergent nucleophilic substitution via synergistic phase-transfer catalysis - Dooley, C; Ibba, F; Botlik, BB; Palladino, C; Goult, CA; Gao, Y; Lister, A; Paton, RS; Lloyd-Jones, GC; Gouverneur, V (Nature Research, 2025)
Catalytic enantioconvergent nucleophilic substitution reactions of alkyl halides are highly valuable transformations, but they are notoriously difficult to implement. Specifically, nucleophilic fluorination is a renowned challenge, especially when inexpensive alkali metal fluorides are used as fluorinating reagents due to their low solubility, high hygroscopicity and Brønsted basicity. Here we report a solution by developing the concept of synergistic hydrogen bonding phase-transfer catalysis. Key to our strategy is the combination of a chiral bis-urea hydrogen bond donor (HBD) and an onium salt—two phase-transfer catalysts essential for the solubilization of potassium fluoride—as a well-characterized ternary HBD–onium fluoride complex. Mechanistic investigations indicate that this chiral ternary complex is capable of enantiodiscrimination of racemic benzylic bromides and α-bromoketones, and upon fluoride delivery affords fluorinated products in high yields and enantioselectivities. This work provides a foundation for enantioconvergent fluorination chemistry enabled through the combination of a HBD catalyst with a co-catalyst specifically curated to meet the requirement of the electrophile.